2020
DOI: 10.2139/ssrn.3660167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender, Test Anxiety and Test Items Scrambling on Students’ Performance in Mathematics: A Quasi-Experimental Study

Abstract: The relative contributions of gender, test anxiety and test items scrambling on performance in Mathematics has been widely assessed, although there is an inconclusive argument regarding the magnitude of such effects. This study was designed to contribute to this debate, while also being the first study to evaluate the interactive effects of the three dimensions of test anxiety (worry, emotion and total) on performance in Mathematics. A systematic random sample of 1,358 SS3 students participated in a quasi-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
(88 reference statements)
1
10
0
Order By: Relevance
“…Curelaru and Diac ( 2021 ) found that low scores in extraversion, agreeableness, conscientiousness, and openness to experience promote high levels of exam anxiety, especially in the cognitive domain. On the other hand, Piemontesi et al ( 2012 ), Ávila Toscano et al ( 2011 ), Manchado Porras and Herví Ortega ( 2021 ), Rana and Mahmood ( 2010 ), Sikhwari ( 2014 ), Owan ( 2020 ) studied the relationship between exam anxiety and academic performance based on a subjective measure such as self-report. Piemontesi and Heredia ( 2011 ), Ávila Toscano et al ( 2011 ), Rana and Mahmood ( 2010 ), Sikhwari ( 2014 ), Owan ( 2020 ) found that the interference dimension was moderately negatively correlated, while lack of confidence also showed a weak negative correlation with academic performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Curelaru and Diac ( 2021 ) found that low scores in extraversion, agreeableness, conscientiousness, and openness to experience promote high levels of exam anxiety, especially in the cognitive domain. On the other hand, Piemontesi et al ( 2012 ), Ávila Toscano et al ( 2011 ), Manchado Porras and Herví Ortega ( 2021 ), Rana and Mahmood ( 2010 ), Sikhwari ( 2014 ), Owan ( 2020 ) studied the relationship between exam anxiety and academic performance based on a subjective measure such as self-report. Piemontesi and Heredia ( 2011 ), Ávila Toscano et al ( 2011 ), Rana and Mahmood ( 2010 ), Sikhwari ( 2014 ), Owan ( 2020 ) found that the interference dimension was moderately negatively correlated, while lack of confidence also showed a weak negative correlation with academic performance.…”
Section: Related Workmentioning
confidence: 99%
“…In their study, it was found that the high factors of tenacity and erudition were the only ones positively associated with academic performance. Therefore, the objective was set to demonstrate that the HFM factors not only predict academic performance but also retain their predictive power beyond the contribution of common psychological predictors such as academic motivation (Baker, 2004 ; Kaufman et al, 2008 ; Petersen et al, 2009 ; Sommer and Dumont, 2011 ; Bailey and Phillips, 2016 ; Orbegoso, 2016 ; Deng and Shi, 2023 ), exam anxiety (Rana and Mahmood, 2010 ; Ávila Toscano et al, 2011 ; Piemontesi and Heredia, 2011 ; Sikhwari, 2014 ; Lomelí-Parga et al, 2016 ; Owan, 2020 ; Manchado Porras and Herví Ortega, 2021 ), and academic procrastination (Sánchez-Hernández, 2010 ; Furlan et al, 2012 ; Delgadová and Gullerová, 2015 ; Kim and Seo, 2015 ; Jones and Blankenship, 2021 ). Furthermore, this study utilized institutional academic performance records, an objective measure, instead of the subjective self-reported measure used by Castro Solano and Cosentino ( 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the amount of time it takes for female individuals to undergo ICT training could compete with the time required to look after children, family obligations and other educational work. Although gender and performance in different subjects is still a debatable topic, studies have also shown its insignificant role on students' performance (Khadijatu, 2017;Lindberg et al, 2010;Owan, 2020;Owan et al, 2019). These studies on gender and performance have an indirect link to the present study since factors such as satisfaction, utilisation of resources, and study habits affect the performance of students.…”
Section: Gender and Students' Satisfaction With The Study Of Ictmentioning
confidence: 99%
“…School performance is traditionally evaluated using grading, after examinations, presentations, submission of assignments and participation in class activities and debates. [ 1 2 3 ] Although examinations or continuous assessment scores are reasonable measures of students’ performance,[ 4 ] there is no universal consensus on the ideal method of testing or on whether components of information processing, such as abilities or conceptual understanding, are more significant. [ 4 5 ] Students should, therefore, strive to achieve acceptable performances in school and afterwards.…”
Section: Introductionmentioning
confidence: 99%